PERAN PENDIDIKAN ORANG TUA DALAM MENINGKATKAN MINAT BELAJAR ANAK PADA SISWA KELAS 1 SDN 05 SEBATAAN DI MASA PANDEMI COVID 19 DI DESA SULUNG TAHUN 2021 - Kurniawan; Parni; Rona (Lunggi Journal, 2025)
This thesis discusses the role of parental education in increasing children's interest in learning children who are still in grade 1 of elementary school. This study aims to: 1) find out the preparation of parents in increasing the learning interest of 1st grade elementary school students during the covid-19 pandemic in Sulung Village. 2) Knowing the role of parental education in Sulung Village in increasing children's interest in learning in 1st grade elementary school students during the covid-19 pandemic. This research is a qualitative descriptive research that aims to determine the role of parental education in increasing children's interest in learning during the covid-19 pandemic. The subjects of this study are parents who have 1st grade children at SDN Sebataan Sulung Village. Data was obtained using research instruments, namely the researcher himself who was assisted by other instruments such as observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data display, conclusion and verification. The results of this study show that parents' preparation in increasing children's interest in learning is more likely to prepare methods and media that can increase the learning interest of 1st grade elementary school children. In addition, the role of parental education in increasing children's interest in learning is very large, because the higher the parent's education, the better the method chosen for their child.